Chemical Control of Correlated Metals as Transparent Conductors. (25th January 2019) - Stoner, Jessica L.; Murgatroyd, Philip A. E.; O'Sullivan, Marita; Dyer, Matthew S.; Manning, Troy D.; Claridge, John B.; Rosseinsky, Matthew J.; Alaria, Jonathan
Abstract: Correlated metallic transition metal oxides offer a route to thin film transparent conductors that is distinct from the degenerate doping of broadband wide gap semiconductors. In a correlated metal transparent conductor, interelectron repulsion shifts the plasma frequency out of the visible region to enhance optical transmission, while the high carrier density of a metal retains sufficient conductivity. By exploiting control of the filling, position, and width of the bands derived from the B site transition metal in ABO3 perovskite oxide films, it is shown that pulsed laser deposition‐grown films of cubic SrMoO3 and orthorhombic CaMoO3 based on the second transition series cation 4d 2 Mo 4+ have superior transparent conductor properties to those of the first transition series 3d 1 V 4+ ‐based SrVO3 . The increased carrier concentration offered by the greater bandfilling in the molybdates gives higher conductivity while retaining sufficient correlation to keep the plasma edge below the visible region. The reduced binding energy of the n =4 frontier orbitals in the second transition series materials shifts the energies of oxide 2p to metal n d transitions into the near‐ultraviolet to enhance visible transparency. The A site size‐driven rotation of MoO6 octahedra in CaMoO3 optimizes the balance between plasma frequency and conductivity for transparent conductor performance. Abstract : The chemical control of the electrical and optical properties of nontoxic, earth abundant Mo‐based correlated metal perovskite oxides optimizes the transparent conductor performance to match the best‐in‐class wide bandgap semiconductors. The use of the three chemically controllable parameters i) carrier density, ii) orbital energy, and iii) bandwidth tune the charge transfer band position, plasma frequency, and conductivity.